Typologie spatio-temporelle de l'ecclesia byzantine : la Mystagogie de Maxime le Confesseur dans la culture philosophique de l'antiquité tardive - Mueller-Jourdan, Pascal. (Vigiliae Christianae, Supplements, 2005)
This study addresses the philosophical context of the Mystagogy of Maximus the Confessor. It examines how the Byzantine monk integrates Neoplatonist topics when exposing one of the most important feature of his religious conception of the physical world or cosmology. The volume contains three chapters. The first one compares the purpose of the Mystagogy and the program of the philosophical training in late Antiquity. The second consists of two parts : (1) study of the use of the Aristotelian categories of 'when' and 'where' in the 'Ambiguum 10' of Maximus in order to analyse the status of ecclesiastical architecture and the nature of the liturgical 'synaxis' of the church (chapter 3); (2) study of the development of the categories of space and time in the works of the Neoplatonist Greek commentators of Plato and Aristotle such as Jamblichus, Proclus, Simplicius and Damascius. The third chapter offers the first extended examination of the metaphysical status of the 'ecclesia' and its dynamic activity compared to the metaphysical status of space and time required for the explanation of the Neoplatonist physical world system. Henceforth, the 'ecclesia' of the Mystagogy can be considered as the type of the providential action of God. This book provides many important new perspectives for reading the works of Maximus the Confessor, especially the Mystagogy, not only for theologians, but also for scholars interested in late Antique and Byzantine philosophy. Cette étude, consacrée au contexte philosophique de la Mystagogie de Maxime le Confesseur, examine comment le moine byzantin intègre certains concepts tirés du Néoplatonisme quand il expose les plus importantes lignes de sa conception religieuse du monde physique. Ce volume contient trois chapitres. Le premier compare l'objectif de la Mystagogie et le programme philosophique des écoles de l'Antiquité tardive. Le second comporte deux parties : (1) une étude de l'emploi des catégories 'quand' et 'où' dans l' Ambiguum 10 ' de Maxime avec pour objectif l'analyse du statut de l'architecture ecclésiale et l'analyse de la nature de la synaxe liturgique (chapitre 3); (2) une étude du développement des catégories de lieu et de temps dans les Oeuvres des Commentateurs néoplatoniciens de Platon et d'Aristote, tels Jamblique, Proclus, Simplicius et Damascius. Le troisième chapitre offre la première étude approfondie du statut métaphysique et dynamique de l' ecclesia compare au statut métaphysique du lieu et du temps requis par l'explication néoplatonicienne du monde physique. L' ecclesia de la Mystagogie sera ainsi considerée comme le type de l'action providentielle de Dieu dans le monde créé. Ce livre fournit une nouvelle perspective de lecture des Oeuvres de Maxime le Confesseur et devrait intéresser tant les théologiens que les scientifiques consacrant leurs travaux à l'Antiquité tardive et à la philosophie byzantine.